The Influence of Interest and Motivation on Investment Decisions Among Management Students - A. Deva Meilany Putri; Wa Ode Rayyani (Penerbit Goodwood, 2025)
Purpose: This study analyzes the influence of investment interest and motivation on the investment decisions of Management Department students, 2023 cohort, at the Faculty of Economics and Business, Universitas Muhammadiyah Makassar, both partially and simultaneously.Methodology: A quantitative approach with a survey method was employed. The population consisted of 35 active students, selected using a total sampling technique. Data were collected through a five point Likert scale questionnaire and analyzed using multiple linear regression, preceded by validity, reliability, and classical assumption tests.Results: Partially, investment interest (t equals 1.383, significance equals 0.176) and investment motivation (t equals 1.302, significance equals 0.202) did not significantly influence investment decisions. Simultaneously, interest and motivation together exerted a positive and significant influence on investment decisions (F equals 19.685, significance equals 0.000), contributing 55.2% of the variance.Conclusions: Investment interest and motivation jointly shape student investment decisions, indicating that these two psychological factors complement one another and operate more effectively when measured together.Limitations: The study is confined to 35 respondents from a single cohort and does not account for other relevant variables such as financial literacy or risk perception.Contributions: The findings provide empirical evidence on student investment behavior and a foundation for more effective financial education programs at higher education institutions.